2015
DOI: 10.15402/esj.v1i1.39
|View full text |Cite
|
Sign up to set email alerts
|

An Institutional Process for Brokering Community-Campus Research Collaborations

Abstract: Knowledge mobilization seeks to identify and support authentic research collaborations between community and university so that benefits of the research accrue to both partners. Knowledge brokering is a key knowledge mobilization mechanism that helps community and university partners connect and build relationships in order to share expertise for mutual opportunity. There remains a need to describe in detail the typical knowledge brokering devices and methodologies. This paper presents a detailed description o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…They have been shown to support community and academic partners in designing and implementing a project, establishing initial connections, delivering skills training, problem-solving, supervising students' community-engaged research and learning activities, evaluating a project's impact, and using results to improve future programs while contributing to positive changes in communities (Keating & Sjoquist 2000;Phipps, Johnny & Wedlock 2015;Tennyson 2014). CCE brokers have also promoted learnings and insights, and addressed concerns of power and resource imbalance by ensuring community and campus partners share control equitably (Keating & Sjoquist 2000;Phipps, Johnny & Wedlock 2015). In addition, because community organisations and universities face high levels of personnel turnover, CCE brokers can help by sustaining a project over the long term (Keating & Sjoquist 2000).…”
Section: Describing and Differentiating Cce Brokering Initiativesmentioning
confidence: 99%
See 3 more Smart Citations
“…They have been shown to support community and academic partners in designing and implementing a project, establishing initial connections, delivering skills training, problem-solving, supervising students' community-engaged research and learning activities, evaluating a project's impact, and using results to improve future programs while contributing to positive changes in communities (Keating & Sjoquist 2000;Phipps, Johnny & Wedlock 2015;Tennyson 2014). CCE brokers have also promoted learnings and insights, and addressed concerns of power and resource imbalance by ensuring community and campus partners share control equitably (Keating & Sjoquist 2000;Phipps, Johnny & Wedlock 2015). In addition, because community organisations and universities face high levels of personnel turnover, CCE brokers can help by sustaining a project over the long term (Keating & Sjoquist 2000).…”
Section: Describing and Differentiating Cce Brokering Initiativesmentioning
confidence: 99%
“…To improve the chances for success when setting up a brokering initiative, Pauzé and Level 8 Leadership Institute (2013) stressed the importance of first identifying the goals of the brokering initiative and then selecting a governance structure accordingly. Further, studies have found that brokering initiatives can benefit from having more formalised administrative infrastructure (Keating & Sjoquist 2000), a clear definition of their relationship with partnerships (Tennyson 2005), established guidelines and tools to address partners' needs (Phipps, Johnny & Wedlock 2015) and flexibility in providing long-term support (Dorow, Stack-Cutler & Varnhagen 2011). CCE brokers must also give significant attention to planning before brokering partnerships and initiating projects.…”
Section: Factors For Successmentioning
confidence: 99%
See 2 more Smart Citations